2007
DOI: 10.1111/j.2007.0030-1299.16188.x
|View full text |Cite
|
Sign up to set email alerts
|

Can a seed bank maintain the genetic variation in the above ground plant population?

Abstract: There are indications that a persistent seed bank can protect small and isolated plant populations from local extinction. Genetic mechanisms contributing to this phenomenon are the increase of local effective population size - and hence the decrease of genetic drift - through a reservoir of persistent seeds, and the accumulation of intergenerational genetic diversity in the seed bank. To find evidence for these mechanisms, we conducted two formal meta-analyses. First, we analyzed 42 published habitat fragmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
161
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(172 citation statements)
references
References 42 publications
6
161
1
1
Order By: Relevance
“…It has been shown that S. chilense has shorter dormancy in stress conditions (i.e., low temperatures), than S. peruvianum (32,33), and variability for dormancy is a heritable trait in these plant species (18) as well as in others (17). Combining these results, we suggest that (i) S. peruvianum may occur in habitats that are more variable across years than those of S. chilense, although temporal variability of climatic conditions has not yet been included in ecological studies (25,30), or that (ii) geographic variability of habitats may promote a longer seed dormancy in S. peruvianum as a generalist strategy to colonize different demes/habitats (13) and reduce risks for extinction following the temporal rescue effect (15). On the other hand, these two wild tomato species differ in their life cycle, with S. chilense being characterized by a generation time of 3 to 7 y (29, 30, 34) and S. peruvianum being characterized by a more variable generation time of 1 to 7 y (34).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…It has been shown that S. chilense has shorter dormancy in stress conditions (i.e., low temperatures), than S. peruvianum (32,33), and variability for dormancy is a heritable trait in these plant species (18) as well as in others (17). Combining these results, we suggest that (i) S. peruvianum may occur in habitats that are more variable across years than those of S. chilense, although temporal variability of climatic conditions has not yet been included in ecological studies (25,30), or that (ii) geographic variability of habitats may promote a longer seed dormancy in S. peruvianum as a generalist strategy to colonize different demes/habitats (13) and reduce risks for extinction following the temporal rescue effect (15). On the other hand, these two wild tomato species differ in their life cycle, with S. chilense being characterized by a generation time of 3 to 7 y (29, 30, 34) and S. peruvianum being characterized by a more variable generation time of 1 to 7 y (34).…”
Section: Resultsmentioning
confidence: 94%
“…The mutation rate is not thought to increase in the seed bank with the age of seeds (8,15). The model parameters are provided in SI Appendix, Table S8.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These populations may still harbor undetected genetic variation. For example, additional alleles may be hidden in the seed bank (Honnay et al 2008), which has been conservatively estimated as averaging 5199 the size of the standing populations (BLM 2011). Our sampling included field collected plants and plants germinated from the seed bank, and there were slight differences in the distribution of genetic diversity (field collected F IS = 0.868 ± 0.06; seed bank F IS = 0.780 ± 0.10) and significant population differentiation between field and seed bank samples (F ST = 0.072; P \ 0.0001).…”
Section: Discussionmentioning
confidence: 99%